1991
DOI: 10.1007/bf02599383
|View full text |Cite
|
Sign up to set email alerts
|

Can residents be trained to counsel patients about quitting smoking?

Abstract: A simple and feasible educational intervention can increase residents' smoking cessation counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(65 citation statements)
references
References 32 publications
0
65
0
Order By: Relevance
“…While we cannot determine causality, it is encouraging that students with more exposure to tobacco counseling education appreciate more the importance of this activity for their future practices, and are more likely to currently counsel their smoking patients. Prior literature (Cornuz et al, 1997;Strecher et al, 1991) also support that training interventions increase smoking cessation counseling.…”
Section: Trainingmentioning
confidence: 95%
“…While we cannot determine causality, it is encouraging that students with more exposure to tobacco counseling education appreciate more the importance of this activity for their future practices, and are more likely to currently counsel their smoking patients. Prior literature (Cornuz et al, 1997;Strecher et al, 1991) also support that training interventions increase smoking cessation counseling.…”
Section: Trainingmentioning
confidence: 95%
“…Despite this, few pediatricians address tobacco, 8 -11 and neither undergraduate medical education 12 nor residency training 13 is adequately preparing the next generation of pediatricians to take up the tobacco challenge. Although efforts to teach pediatric residents to intervene on tobacco hold considerable promise, 14,15 few programs include in their curriculum comprehensive training in intervention on tobacco, and pediatric residents are less active in the area of tobacco intervention than are residents in other medical disciplines. 16 Shortcomings in pediatric training and practice represent important gaps in the United States' efforts to protect young people from tobacco-related disease and addiction.…”
mentioning
confidence: 99%
“…A meta-analysis done in 1988 by Kottke et al showed an overall cessation rate of 8.4% at six months with brief (less than 15 minutes) physician's advise. Since then, there have been several large studies on physician's advise that have shown quit rates of up to 10 percent, (Cummings et al 1889, Strecher et al 1991 At week 12, the mean FTND score for smokers was 2.33 (±0.862) in pharmacotherapy group versus 1.09 (±0.578) in the combined therapy group, (P=0.002) and FTND-ST score for smokeless tobacco users was 2.66 (±1.52) in pharmacotherapy group versus 1.73 (±1.823) in the combined therapy group, (P=0.039, t=2.11), showed significant reduction in score. The cessation rate for smokeless tobacco in combined group was nearly double that of pharmacotherapy group 53.85% and 28.12%, respectively and cessation rate in smokers were 33.33% in pharmacotherapy group alone and 54.54% in combined group.…”
Section: Discussionmentioning
confidence: 99%